Austropeplea ollula (Pulmonata: Lymnaeidae): A new molluscan intermediate host of a human intestinal fluke, Echinostoma cinetorchis (Trematoda: Echinostomatidae) in Korea - Chung, Pyung-Rim (The Korean Society for Parasitology, 2001)
Three freshwater snail species of the family Lymnaeidae have been reported from Korea, Radix auricularia coreana, Austropeplea ollula and Fossaria truncatula. Out of 3 lymnaeid snail species, A. ollula was naturally infected with the Echinostoma cinetorchis cercariae (infection rate = 0.7%). In the experiments with the laboratory-bred snails, F. truncatula as well as A. ollula was also susceptible to the E. cinetorchis miracidia with infection rates of 25% and 40%, respectively. All of three lymnaeid snail species exposed to the E. cinetorchis cercariae were infected with the E. cinetorchis metacercariae. It is evident that A. ollula acts as the first molluscan intermediate host of E. cinetorchis in Korea, and F. truncatula may be a possible candidate for the first intermediate host of this intestinal fluke. Also, three lymnaeid snail species targeted were experimentally infected with E. cinetorchis metacercariae.